Kyoto A Creative City : Leveraging Creativity for City Competitiveness and Inclusive Urban Transformation - Mulas, Victor (World Bank, Washington, DC, 2021)
This report builds on the findings from the Technical Deep Dive (TDD) ‘Creative Cities: Case of Kyoto,’ organized by the Tokyo Development and Learning Center (TDLC) in partnership with UNESCO and the City of Kyoto in January 2020. The TDD focused on the framework for developing creative cities and the impact that creative industries can have on cities’ spatial, economic, and social development. Using the case of Kyoto in Japan, the TDD highlighted the different components of creative neighborhoods and communities and how to build them. This report uses the case of Kyoto to demonstrate how city planners and the local private sector can collectively build creative communities. It builds on an important conversation on how to leverage creative cities to safeguard inclusive economic development and catalyze urban spaces that enhance economic, urban, and social development. Insights for this report were derived from a literature review along with interviews with practitioners with a focus on creative clusters and spatial transformation. Social inclusion is also a theme that we discuss in the report, though to a lesser degree because of data constraints. This report provides distilled practical lessons and key insights for policy makers and practitioners interested in applying the concept of creative cities effectively. Using the case of Kyoto, the report analyzes how creative communities and policy action can be leveraged for urban transformation not only at the neighborhood level but also citywide and beyond.